Legal Status of Business Entities on the Merger of Subsidiaries of BUMN into BUMN (Case Study of Indonesian Sharia Bank) - Andriana Kusumawati; Gunawan Nachrawi; Misbahul Huda (LEGAL BRIEF, 2022)
The background of the research was the merger process of three sharia banks, subsidiaries of BUMN, namely BRIS, BSM, and BNIS into one business entity, Bank Syariah Indonesia (BSI). This is done by the Government for BSI to become the world's Top 10 and Indonesia to become the World Halal Center. The research is to analyze the position of PT Bank Syariah Indonesia as a subsidiary of BUMN on separated state assets and the status of BSI's legal entity in order to become a BUMN through State Equity Participation (PMN). The normative juridical research method is presented with a systematic description and qualitative analysis. The results of the research that BSI as a subsidiary is not included in the separated state assets. BSI is still a subsidiary of a BUMN because there is no direct capital investment from the state, so there needs to be a PMN so that BSI becomes a BUMN. There are two ways of PMN, by reducing the state capital of the three SOEs by the amount of shares or capital in BSI so that the shares become direct capital from the State in BSI. The second method is to inject Series A Dwiwarna Shares into BSI so that the State has special rights over BSI.